THE IMPACT OF SERVICE QUALITY, PRODUCT QUALITY, AND BRAND IMAGE ON CUSTOMER LOYALTY THROUGH THE MEDIATION OF CUSTOMER SATISFACTION AMONG PRIMA FRESHMART CUSTOMERS - Layarda, Meiryanti; Achmadi, Hendra (Transpublika Publisher, 2024)
As the retail industry for fresh produce in Indonesia becomes increasingly competitive, it creates an urgency for retailers to maintain relevant position in the market. Retailers need to cultivate loyal customers to ensure sustained performance and growth. Prima Freshmart, a specialized retailer that focuses on poultry products, is currently dealing with the challenge of having low customer loyalty rates based on the results of a preliminary survey. In order to understand how service quality, product quality, and brand image impact customer loyalty among Prima Freshmart's clientele, a study was conducted with 194 participants who completed questionnaires. The data was then analyzed using SmartPLS 4 software. The findings indicate that service quality, product quality, and brand image have a significant and positive influence on customer satisfaction. Furthermore, customer satisfaction has a significant and positive effect on customer loyalty and acts as a mediator in the relationship between service quality, product quality, brand image, and customer loyalty. These discoveries offer potential guidance for Prima Freshmart's management to enhance service quality, product quality, and brand image in order to improve customer satisfaction and loyalty. This research provides valuable insights that can be applied to both theoretical and practical aspects of customer retention strategies in the retail sector.